Corporate Social Responsibility Practices and Environmentally Responsible Behavior: The Case of The United Nations Global Compact - Cetindamar, Dilek (Journal of business ethics, 2007)
The aim of this paper is to shed some light on understanding why companies adopt environmentally responsible behavior and what impact this adoption has on their performance. This is an empirical study that focuses on the United Nations (UN) Global Compact (GC) initiative as a Corporate Social Responsibility (CSR) mechanism. A survey was conducted among GC participants, of which 29 responded. The survey relies on the anticipated and actual benefits noted by the participants in the GC., The results, while not conclusive, indicate that companies have more than one reason for adopting environmentally responsible behavior and that ethical and economic reasons co-exist. In terms of performance, the impact of participation in the GC seems to be particularly high in securing network opportunities and improved corporate image. The results indicate that companies that have participated many years in the GC, have submitted the most projects and have attended the most GC meetings also regard their CSR involvement as having had a strong, positive influence on their market performance. GC participation does not result in significant cost advantages, but this does not seem to have been regarded as a goal anyway. Costs seem to be affected to a␣large extent by existence of in-house research and␣development and the capability of developing environmentally sound technologies. Overall, the company receives both ethical and economic benefits from joining the GC.